Modulation Format Recognition Using Artificial Neural Networks for the Next Generation Optical Networks (2021)
Transmission systems that use advanced complex modulation schemes have been driving the growth of optical communication networks for nearly a decade. In fact, the adoption of advanced modulation schemes and digital coherent systems has led researchers and industry communities to develop new strategies for network diagnosis and management. A prior knowledge of modulation formats and symbol rates of all received optical signals is needed. Our approach of modulation formats identification is based on artificial neural networks (ANNs) in conjunction with different features extraction approaches. Unlike the existing techniques, our ANN-based pattern recognition algorithm facilitates the modulation format classification with higher accuracies.